Finding the n Most Vital Links in Flow Networks - Ratliff, H. Donald; Sicilia, G. Thomas; Lubore, S. H. (Management Science, 1975)
The n most vital links of a flow network are defined as those n arcs whose simultaneous removal from the network causes the greatest decrease in the throughput capability of the remaining system between a specified pair of nodes. These n arcs are shown to be the n largest capacity arcs in a particular cut. A solution procedure is developed which involves sequentially modifying the network so as to make this cut eventually become the cut with smallest capacity. An algorithm with computational results is presented.